Decision-making under uncertainty in environmental health policy: new approaches - Jacques Reis; Peter S. Spencer (Komiyama Printing Co. Ltd, 2019)
Abstract Decision-making in environmental health policy is a complex procedure even in well-known conditions. Thus, in the case of uncertainty, decision-making becomes a hurdle race. We address scientific uncertainty, methods to reduce uncertainty, biomedical doubt and science communication, and the role of stakeholders, activists, lobbies and media that together influence policy decisions. We also consider the major responsibility and role of the medico-scientific community in this process. This community can and should teach the principle of scientific uncertainty to all stakeholders, advise policy-makers and underline the ethical issues, considering that our brains are not only the deposit of our humanity but also the route to environmental health and societal harmony.